2020
DOI: 10.1136/bmjdrc-2020-001206
|View full text |Cite
|
Sign up to set email alerts
|

Role of resistin, IL-6 and NH2-terminal portion proBNP in the pathogenesis of cardiac disease in type 2 diabetes mellitus

Abstract: IntroductionEpidemiological and genetic studies have recorded the association between proinflammatory cytokines and the development of insulin resistance, diabetes, and cardiovascular disease. The role of interleukin 6 (IL-6), NH2-terminal portion pro-brain natriuretic peptide (NT-proBNP) and resistin in the pathogenesis of heart disease in type 2 diabetes mellitus (T2DM) is still a matter of controversy. The current study aimed to evaluate the role of these biomarkers in the development of left ventricular sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(48 reference statements)
1
7
1
Order By: Relevance
“…Our data are in accordance with several studies showing that resistin plays a major regulatory role in the inflammatory response [48,49]. Resistin has also been reported to upregulate the expression of proinflammatory cytokines such as TNF-α, IL-6, IL-12, and monocyte chemoattractant protein in PBMCs, macrophages, and hepatic stellate cells via the nuclear factor-κB pathway [47,50]; the correlation of resistin levels with inflammatory and fibrinolytic markers has been reported both in the general population and in individuals with T2DM, coronary atherosclerosis, chronic kidney disease, rheumatoid arthritis, and/or sepsis [48,49,51].…”
Section: Resisɵn Levelssupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are in accordance with several studies showing that resistin plays a major regulatory role in the inflammatory response [48,49]. Resistin has also been reported to upregulate the expression of proinflammatory cytokines such as TNF-α, IL-6, IL-12, and monocyte chemoattractant protein in PBMCs, macrophages, and hepatic stellate cells via the nuclear factor-κB pathway [47,50]; the correlation of resistin levels with inflammatory and fibrinolytic markers has been reported both in the general population and in individuals with T2DM, coronary atherosclerosis, chronic kidney disease, rheumatoid arthritis, and/or sepsis [48,49,51].…”
Section: Resisɵn Levelssupporting
confidence: 93%
“…A recent study conducted in subjects with and without ventricular dysfunction showed resistin levels were overall comparable to that of our study, and correlated with IL-6 and HDL-C/TG, but not with renal function as in our study. Younger mean age of participants [50] may partly explain the observed differences with our study.…”
Section: Resisɵn Levelscontrasting
confidence: 86%
“…This study also found that resveratrol can increase adiponectin levels and reduce resistin levels. Resistin can reduce the uptake of glucose by adipose tissue and inhibit the signal transduction pathway of insulin [ 23 ]. Adiponectin can reduce the occurrence and development of diabetes by improving insulin sensitivity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistin, which is a polypeptide associated with type 2 diabetes [ 4 ], was named for its effect of causing insulin resistance and inducing secondary elevated blood glucose levels in diabetic patients [ 5 , 6 ]. Resistin is a 12.5 kD protein that is rich in cysteine and is mainly produced by activated white blood cells or adipose tissue.…”
Section: Introductionmentioning
confidence: 99%